Histopathological Terminology Standards for the Reporting of Prostatic Epithelial Lesions in Dogs. (August 2019) - Palmieri, C.; Foster, R.A.; Grieco, V.; Fonseca-Alves, C.E.; Wood, G.A.; Culp, W.T.N.; Murua Escobar, H.; De Marzo, A.M.; Laufer-Amorim, R.
Summary: The terminology applied to canine prostatic epithelial lesions, especially carcinomas, is currently not standardized and this hampers the ability of pathologists to study the biological and clinical significance of these lesions. The aim of this review is to present the essential histomorphological diagnostic attributes of a wide spectrum of prostatic epithelial lesions in dogs. In addition to the traditionally recognized prostatic hyperplasia, hormonal atrophy, prostatitis, squamous metaplasia, adenocarcinoma and transitional cell (urothelial) carcinoma, new entities are described and discussed in order to provide veterinary pathologists with a basic atlas of common histological lesions of the canine prostate that is comprehensive and easy to use.